Value of urodynamic findings in predicting upper urinary tract damage in neuro‐urological patients: A systematic review. Issue 5 (2nd February 2018) - Musco, Stefania; Padilla‐Fernández, Barbara; Del Popolo, Giulio; Bonifazi, Matteo; Blok, Bertil F. M.; Groen, Jan; 't Hoen, Lisette; Pannek, Jürgen; Bonzon, Jerome; Kessler, Thomas M.; Schneider, Marc P.; Gross, Tobias; et al.
Abstract : Aim: The main goals of neurogenic lower urinary tract dysfunction (NLUTD) management are preventing upper urinary tract damage (UUTD), improving continence, and quality of life. Here, we aimed to systematically assess all available evidence on urodynamics predicting UUTD in patients with NLUTD. Methods: A systematic review according to the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses (PRISMA) Statement was performed in March 2017. Only neuro‐urological patients assessed by urodynamics were included. Any outcome of upper urinary tract function were evaluated. Results: Forty‐nine studies (1 randomized controlled trial, 9 prospective, and 39 retrospective case series) reported urodynamic data on 4930 neuro‐urological patients. Of those, 2828 (98%) were spina bifida (SB) children. The total number of adults was 2044, mainly having spinal cord injury (SCI) (60%). A low bladder compliance was found in 568 (46.3%) and 341 (29.3%) of the paediatric and adult population, respectively. Hydronephrosis (HDN) was detected in 557 children (27.8%) in 19/28 studies and 178 adults (14.6%), mainly SCI, in 14/21 studies. Nine out of 30 multiple sclerosis (MS) patients affected by HDN (16.8%) showed low compliance in 4/14 studies. Conclusions: Patients with SB and SCI have a higher risk of developing UUTD (mainly reported as HDN) compared to those with MS. Reduced compliance and high DLPP were major risk factors for UUTD. Although our findings clarify the mandatory role of urodynamics in the management of NLUTD, standardization and better implementation of assessments in daily practice may further improve outcomes of neuro‐urological patients based on objective measurements, that is, urodynamics.